Prevention of oculopharyngeal muscular dystrophy by muscular expression of Llama single-chain intrabodies in vivo. - Chartier, A.; Raz, V.; Sterrenburg, E.; Verrips, C.T.; van der Maarel, S.M.; Simonelig, M. (Human Molecular Genetics, 2009)
Oculopharyngeal muscular dystrophy (OPMD) is a late onset disorder characterized by progressive weakening of specific muscles. It is caused by short expansions of the N-terminal polyalanine tract in the poly(A) binding protein nuclear 1 (PABPN1), and it belongs to the group of protein aggregation diseases, such as Huntington's, Parkinson's and Alzheimer diseases. Mutant PABPN1 forms nuclear aggregates in diseased muscles in both patients and animal models. Intrabodies are antibodies that are modified to be expressed intracellularly and target specific antigens in subcellular locations. They are commonly generated by artificially linking the variable domains of antibody heavy and light chains. However, natural single-chain antibodies are produced in Camelids and, when engineered, combined the advantages of being single-chain, small sized and very stable. Here, we determine the in vivo efficiency of Llama intrabodies against PABPN1, using the established Drosophila model of OPMD. Among six anti-PABPN1 intrabodies expressed in muscle nuclei, we identify one as a strong suppressor of OPMD muscle degeneration in Drosophila, leading to nearly complete rescue. Expression of this intrabody affects PABPN1 aggregation and restores muscle gene expression. This approach promotes the identification of intrabodies with high therapeutic value and highlights the potential of natural single-chain intrabodies in treating protein aggregation diseases.